2023
DOI: 10.53894/ijirss.v6i2.1328
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial innovation among international students in the UAE: Differential role of entrepreneurial education using SEM analysis

Abstract: This paper explores the impact of entrepreneurial education among international students studying higher education in the UAE. The authors examine the role of entrepreneurial education as an independent variable and as a moderating variable in the relationship between external factors (measured by the economy, institutions and society) and internal factors (measured by entrepreneurial orientation, entrepreneurial capabilities and achievement) on entrepreneurial innovation. A survey approach was used in which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 84 publications
(146 reference statements)
0
1
0
Order By: Relevance
“…According to Khalfan (2017), there is a tendency for males to exhibit a higher level of care towards community and shared experiences, which potentially amplifies the social and cultural aspects of memes. In contrast, Dash et al (2023) and Shwedeh et al (2023b) found that women reported experiencing favorable outcomes, including heightened exposure, humor, and interdisciplinary teamwork. These findings strongly emphasize the entertainment and collaborative aspects among female participants.…”
Section: Discussion and Analysismentioning
confidence: 91%
“…According to Khalfan (2017), there is a tendency for males to exhibit a higher level of care towards community and shared experiences, which potentially amplifies the social and cultural aspects of memes. In contrast, Dash et al (2023) and Shwedeh et al (2023b) found that women reported experiencing favorable outcomes, including heightened exposure, humor, and interdisciplinary teamwork. These findings strongly emphasize the entertainment and collaborative aspects among female participants.…”
Section: Discussion and Analysismentioning
confidence: 91%
“…The relationship between smart applications and TQM regulations is also evident in the economic domain (Allam et al, 2022;Salloum et al, 2023b). Scholarly research suggests that favorable tax incentives and regulatory frameworks might draw investments and stimulate the emerging smart applications-related industries (Dubey et al, 2022;Dwivedi et al, 2022).…”
Section: Relationship Of Tqm Policies and Regulations For Promoting E...mentioning
confidence: 99%
“…According to this study, technological adaptation is the process by which businesses, both public and private, are able to engage with technology advancements in an effective and efficient manner (Dahlman et al, 1987;Ghavifekr & Rosdy, 2015;Shwedeh et al, 2023b). Because of this, the technological adaptability measurement items were derived from a variety of studies, including but not limited to Djokovic and Souitaris (2008), Kintu, Zhu, and Kagambe (2017), Reguera andLopez (2021), andSelim (1907).…”
Section: Technology Adaptabilitymentioning
confidence: 99%
“…The pivotal role of entrepreneurship becomes apparent when its inherent capacity to identify and seize promising business opportunities is considered [ 7 ]. Exposing a community to entrepreneurial education increases its ability to exploit novel businesses [ 8 ], and these entrepreneurial activities accelerate economic growth [ 9 ] and sustainable development [ 10 ]. Although they are often applied in broader regional contexts [ 11 ], the foundational concepts of entrepreneurship are equally pertinent in rural settings.…”
Section: Introductionmentioning
confidence: 99%